An Examination of the Loyalhanna Limestone's Structural Features and Their Impact on Mining and Ground Control Practices - Tony Iannacchione (International Conference on Ground Control in Mining, 2002)
A close look at the Loyalhanna Limestone of southwestern Pennsylvania reveals a complex structural environment. Most exposures of the Loyalhanna occur along Chestnut Ridge and Laurel Hill within the Allegheny Mountain Section of the Appalachian Plateaus Province. Because the Loyalhanna is rated as a super pavement aggregate by the Pennsylvania Department of Transportation and because of its proximity to the population centers of southwestern Pennsylvania, the Loyalhanna has been extensively mined along these prominent anticlinal structures. Geologic and engineering analyses were performed using gas well and core logs, outcrop examinations, underground observations, and mine maps. Strata exposures from both outcrops and quarries were used to construct geologic maps, stereonet, and rose diagram projections so that the Loyalhanna's structural environment could be understood better. Many of these structural conditions cause ground control problems at local quarries. These problems ranged from small-to-moderate sized rock falls associated with roof jointing to pillar failures associated with dipping discontinuities. Stresses ranged from tensional on structural domes where weathering dominates, to high levels of compression within structural saddles. A greater understanding of these characteristics is a prerequisite to develop engineering controls, such as improved mine layouts. pillar sizes, etc., that lessen miner exposure to these hazards.